2005
DOI: 10.1021/ic049081g
|View full text |Cite
|
Sign up to set email alerts
|

Cations M2(O2CtBu)4+, Where M = Mo and W, and MoW(O2CtBu)4+. Theoretical, Spectroscopic, and Structural Investigations

Abstract: With the aid of density function theory, the molecular and electronic structures of the molecules Mo2(O2CMe)4, MoW(O2CMe)4, and W2(O2CMe)4 and their single-electron oxidized radical cations have been determined; this includes calculated observables such as v(MM) and the delta --> delta* electronic transition energies. The calculated properties are compared with those for the corresponding pivalates, M2(O2CtBu)4 (M = Mo or W) and MoW(O2CtBu)4 and their radical cations prepared in situ by oxidation with Cp2FePF6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 41 publications
5
52
1
Order By: Relevance
“…Actually, the main problem with semi-empirical theories such as ZINDO/S is that, contrary to ab initio approaches, it is very difficult to know beforehand for which type of structure the predictions are likely to be meaningful or not [6]. Actually, the Time-Dependent Density Functional Theory (TD-DFT) originally proposed more than two decades ago by Runge and Gross [7], has become the most widely used tool for theoretically evaluating excited state energies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This success is due to its efficiency to quickly provide an accurate description of transition energies.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the main problem with semi-empirical theories such as ZINDO/S is that, contrary to ab initio approaches, it is very difficult to know beforehand for which type of structure the predictions are likely to be meaningful or not [6]. Actually, the Time-Dependent Density Functional Theory (TD-DFT) originally proposed more than two decades ago by Runge and Gross [7], has become the most widely used tool for theoretically evaluating excited state energies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This success is due to its efficiency to quickly provide an accurate description of transition energies.…”
Section: Introductionmentioning
confidence: 99%
“…This compares to PCET self-exchange rates observed in related metal complexes. 12 Previous studies have shown that electron transfer rates for PCET self-exchange reactions are often located between the EPR and electrochemical timescales, such as or AgPF6 in CD2Cl2 proved to be unsuccessful. The generated paramagnetic species gave rise to a spectrum that displayed excessive broadening, from which no characteristic resonances could be identified for the solvate.…”
Section: Mechanistic Insight Into Proton-coupled Mixed Valencymentioning
confidence: 99%
“…[4] An umber of supported dinuclear metalloradicals with two metal atoms held together to form ab ond by ab ridging ligand are known. [5] In contrast, stable but unsupported dinuclear metalloradicals are rare.Recently two unsupported dinuclear metalloradicals were isolated and studied by single crystal Xray diffraction, that is,[ M 2 Cp 2 (CO) 4 (PMe 3 ) 2 ]C + (M = Mo and W), where two metal atoms are held together by am ultiple bond (bond order = 1.5) with assistance from the electrondonating ligand PMe 3 . [6] Cobalt complexes have been widely used as efficient catalysts for organic transformations and CÀFb ond activations, [7] but the chemistry of dicobalt metalloradicals is relatively underdeveloped.…”
Section: (Co) 2 ]Cmentioning
confidence: 99%